Penguatan Pengetahuan Dan Pelaksanaan Kegiatan Intervensi Terkait Hipertensi Pada Kader Dan Masyarakat - Novianus, Cornelis; Inaku, Awaludin Hidayat Ramli; ., Adinda; Anjani, Intan Sulistia; Yunita, Norma; Maulidin, Ilham; Rahmadani, Putri Fathiah (IFI cabang Kota Bekasi, 2024)
Based on data from the Elderly Posbindu, PTM Posbindu, and a preliminary study conducted on residents of RW.02 Pondok Jaya Village, District Pondok Aren, South Tangerang City shows that RW.02 has the highest hypertension rate compared to other RW. Responding to existing health problems, it is necessary to carry out public health interventions in order to address health problems in that location. The implementation method that has been carried out in Field Learning Experience (PBL) activities with 4 stages, namely the plan of action stage, implementation stage, monitoring stage, evaluation stage. The plan of action stage is the preparation of an intervention program plan based on the results of the Village Community Consultation (MMD). The implementation stage has 2 activities, the first is Empowering Active, Independent, and Able to Handle Hypertension Cadres (AMUNISI) and Empowering Hypertension Aware Families (GADARSI). The monitoring stage is carried out during joint visits between groups and cadres to the RW 02 community door to door by recording blood pressure and checking the drug compliance sheet. In the evaluation stage, it is known that the Wilcoxon test p-value is 0.007 which shows that the increase in cadre knowledge before education is smaller than after education and the p-value is <0.0001 which shows that there is an increase in community knowledge before education is given smaller than after education.